Paying a Premium on Your Premium? Consolidation in the US Health Insurance Industry - Dafny, Leemore; Duggan, Mark; Ramanarayanan, Subramaniam (The American economic review, 2012)
We examine whether and to what extent consolidation in the US health insurance industry has contributed to higher employer-sponsored insurance premiums. We exploit the differential impact across local markets of a national merger of two insurers to identify the causal effect of concentration on premiums. Using data for large groups, we estimate premiums in average markets were approximately seven percentage points higher by 2007 due to increases in local concentration from 1998–2006. We also find evidence consolidation facilitates the exercise of monopsonistic power vis-à-vis physicians, leading to reductions in their absolute employment and earnings relative to other healthcare workers. JEL: G22, I13